Perancangan Dan Implementasi Aplikasi Massive Open Online Course (MOOC) Modul Certificate Dan Ceremony - Risti Sari Achya; Rahmat Inggi; La Ode Bakrim (Jurnal Sistem Informasi dan Sistem Komputer, 2022)
Advances in information technology change the process of exchanging information and educational models. Along with the development of the times, various distance education platforms have emerged or better known as MOOC (Massive Open Online Course). With a learning model and certificates that are equivalent to formal education, MOOC is an alternative in today's world of education. The role of certificates in the world of work and academics is very important, because it is the identity of a person's expertise in a field. However, the process of managing certificates to submission must be carried out at the implementing institutions. This is a problem for those who live far from the educational institution. In addition, the occurrence of natural disasters causes potential damage to the certificate to be an additional problem. The problem of distance also causes the management and registration process to be less efficient. While taking the certificate has the condition that it has followed the graduation process. With these factors, the author will design an efficient MOOC certificate and ceremony module in the certificate and graduation management process so as to reduce the risk of data or information loss.